Monitoring the decade of action for global road safety 2011–2020: An update - Hyder, A; Paichadze, N; Toroyan, T; Peden, M (Routledge, 2016)
The United Nations Road Safety Collaboration (UNRSC) was set up in 2004 in response to the recognised need for the United Nations (UN) system to encourage efforts to address the global road safety crisis. In 2010, the UN General Assembly Resolution 64/255 declared 2011–2020 the Decade of Action for Road Safety with the overarching goal of stabilising and reducing the forecasted number of road traffic deaths by increasing activities at national, regional and global levels. In 2011, a Plan of Action for the Decade of Action, a tool to support the development of national and local plans of action, was launched. Countries are encouraged to implement activities according to the five pillars set out by the Plan of Action. The UNRSC, tasked to evaluate the overall impact of the Decade, developed and populated indicators for each pillar. Currently, 36 of 38 proposed indicators are populated by baseline data for 2010 from the second Global status report for road safety. However, gaps exist in data quality and availability on a global level. Therefore, there is an urgent need for improving data quality and availability to measure the progress of the Decade of Action.